Language Contact, Cognition, and Cross-Linguistic Influence in the Greek Pentateuch - Maurais, Jean (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2022)
This study engages recent discussions concerning the description of the Greek of the LXX Pentateuch and the nature of source text interference. Research in contact linguistics and cognition provides a framework to describe the various phenomena observed, ranging from borrowing of linguistic material to the more widespread structural transfer. Processes such as pivot-matching and the cognitive aspects of word-choice transfer shed light on the mechanics of translation and issues such as the nature of cross-linguistic influence and a translator’s apparent inconsistencies. In this context, the intelligibility of specific renderings or their grammatical conventionality are not sufficient criteria for assessing cross-linguistic influence since its effects can be felt at the level of register or genre. This has important ramifications for the register or genre categorization of various textual units of the LXX Pentateuch and stylistic descriptions.